2014
DOI: 10.15835/nbha4219414
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Relationships in Local Varieties of Eggplant from Different Cultivar Groups as Assessed by Genomic SSR Markers

Abstract: Spain is a secondary center of diversity for eggplant (Solanum melongena). Spanish landraces of eggplant are normally classified in four cultivar groups: Round, Listada de Gandía, Semi-Long, and Long. We have used 19 genomic SSRs for the molecular characterization of 30 eggplant accessions corresponding to the four cultivar groups. Sixteen SSRs of which 15 were polymorphic could be amplified and 65 polymorphic alleles, with a range of two to 11 alleles/locus, were detected. The polymorphism information content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…In addition, the number of alleles/locus in the whole collection was high (4.6), higher than that (3.67) revealed by Augustinos et al [23], when they studied a limited number of Greek traditional eggplant cultivars. Taking into consideration other studies on eggplants from different geographic origin or different cultivar types based on SSR data, the number of alleles/locus calculated in our eggplant collection is lower than that detected by Hurtado et al [35] and Liu et al [36], but almost similar to those by Demir et al [74], Muñoz-Falcón et al [73], Tümbilen et al [66], and Vilanova et al [50,75]. Two of the SSR markers used in our study (csm27, csm32), have also been used by Hurtado et al [35] and Vilanova et al [50].…”
Section: Molecular Diversitysupporting
confidence: 85%
See 2 more Smart Citations
“…In addition, the number of alleles/locus in the whole collection was high (4.6), higher than that (3.67) revealed by Augustinos et al [23], when they studied a limited number of Greek traditional eggplant cultivars. Taking into consideration other studies on eggplants from different geographic origin or different cultivar types based on SSR data, the number of alleles/locus calculated in our eggplant collection is lower than that detected by Hurtado et al [35] and Liu et al [36], but almost similar to those by Demir et al [74], Muñoz-Falcón et al [73], Tümbilen et al [66], and Vilanova et al [50,75]. Two of the SSR markers used in our study (csm27, csm32), have also been used by Hurtado et al [35] and Vilanova et al [50].…”
Section: Molecular Diversitysupporting
confidence: 85%
“…Low H o was also detected by Augustinos et al [23] and Liu et al [36] (0.04 and 0.03, respectively) and Vilanova et al [50,75]. The high level of homozygosity in eggplant landraces shows that pure lines can easily be derived by individual selection from these materials [75]. Although genetic diversity based on molecular data is dependent on the type and number of markers used and the accessions tested [66], the relatively high PIC values and average number of alleles/locus detected and also the high levels of heterozygosity observed compared to other similar studies, indicate that considerable diversity exists in our eggplant collection.…”
Section: Molecular Diversitymentioning
confidence: 50%
See 1 more Smart Citation
“…Using 4 SSR markers, a total of 44 alleles were detected among the 48 brinjal genotypes. The average number of allele per locus was 11, with a range of 9 (smSSR03) to as many as 14 (smSSR01) which is supported by Vilanova et al (2014), they found 2 to 11 alleles/locus by using 19 genomic SSRs for the molecular characterization of 30 eggplant accessions; the number of alleles ranged from 2 to 8 with a mean of 4.3 alleles per marker recorded by Caguiat and Hautea (2014), Adeniji et al (2012) observed a total of 417 alleles amplified with the number of alleles ranging from 5 (EM 141) to 38 (EM 120 b), Verma et al (2012) recorded the number of alleles per primer ranging from 2 to 10, with a mean of 4.67; Sunseri et al (2010) found the number of alleles ranging from 2 to 7 with an average of 4.5. Nearly similar observation was found by Li et al (2003) where they ranged from 2 alleles to 11 alleles with an average of 6.61 alleles per locus in chilli.…”
Section: Discussionmentioning
confidence: 73%
“…As a measure of the informativeness of microsatellites, the PIC value ranges from a low of 0.6413 (smSSR14) to a high of 0.8536 (smSSR11) and averaged 0.7660 (Table 3). The results of the study supported by Vilanova et al (2014), recorded the polymorphism information content (PIC) of SSR markers ranging from 0.07 to 0.77, with an average value of PIC=0.50. Also SSRs was selected by Caguiat and Hautea (2014) based on their high polymorphism information content (PIC) and the high quality of bands.…”
Section: Discussionmentioning
confidence: 74%